Uterine Transplant Optimization From a Preclinical Donor Model With Controlled Cardiocirculatory Arrest - Emma Loiseau, MSc; Benoit Mesnard, MSc; Sarah Bruneau, PhD; Carla De Sousa, MD; Stéphanie Bernardet, PhD; Jeremy Hervouet; David Minault; Stephan Levy, MSc; Antoine Le Gal, MD; Ludivine Dion, PhD; Gilles Blancho, MD, PhD; Vincent Lavoue, MD, PhD; et al. (Transplantation Direct)
Background. Uterus transplantation from deceased donors offers a promising solution to the organ shortage, but optimal preservation methods are crucial for successful outcomes. Our primary objective is to conduct an initial assessment of the contribution of oxygenated hypothermic perfusion in uterine transplantation. Methods. We performed a preclinical study on a porcine model of controlled donation after circulatory death (60 min warm ischemia). Ten uterus grafts were preserved for 12 h using static cold storage or hypothermic machine perfusion (VitaSmart device, perfusion pressure at 15 mm Hg). Subsequently, they were reperfused using ex vivo normothermic machine perfusion (Liverassist, perfusion pressure at 30 mm Hg) with oxygenated autologous blood to assess early ischemia/reperfusion injury. Not only resistance index assessment and oxygenation evaluation but also immunochemistry and gene expression analysis were performed. Results. This study demonstrates the feasibility of using hypothermic machine perfusion for uterine graft preservation, showing improvements in reperfusion capacity (decrease of resistance indexes; P < 0.0001) and tissue oxygenation (higher oxygen level) compared with static cold storage. Conclusions. These findings provide valuable insights for further research and refinement of uterine transplantation procedures.